2012
DOI: 10.1186/ar3895
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine is associated with impaired interferon-alpha and tumor necrosis factor-alpha production by plasmacytoid dendritic cells in systemic lupus erythematosus

Abstract: IntroductionPlasmacytoid dendritic cells (pDCs) constitutively express two members of the Toll-like receptor (TLR) family, TLR-9 and TLR-7, through which they can be stimulated to produce high levels of interferon (IFN)-α, a key mediator of the pathogenesis of systemic lupus erythematosus (SLE). Given the known efficacy of hydroxychloroquine (HCQ) in the treatment of SLE, we examined its ability to inhibit such pDC function in vivo.MethodsPeripheral blood mononuclear cells (PBMCs) from SLE subjects treated or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
153
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(174 citation statements)
references
References 34 publications
13
153
3
5
Order By: Relevance
“…It is thought to block Toll-like receptors (TLR), reducing the activation of dendritic cells. In vitro plasmacytoid dendritic cells from SLE patients treated with hydroxychloroquine showed an impaired ability to produce interferon-α (IFN-α) and tumor necrosis factor-α when stimulated with TLR-9 and TLR-7 agonists [152]. In addition to its efficacy in preventing flares of SLE, there is epidemiological evidence [74,98,153] that it may be cardioprotective, possibly by improving the lipoprotein profile [154] and improving vessel elasticity [155].…”
Section: Hydroxychloroquinementioning
confidence: 99%
“…It is thought to block Toll-like receptors (TLR), reducing the activation of dendritic cells. In vitro plasmacytoid dendritic cells from SLE patients treated with hydroxychloroquine showed an impaired ability to produce interferon-α (IFN-α) and tumor necrosis factor-α when stimulated with TLR-9 and TLR-7 agonists [152]. In addition to its efficacy in preventing flares of SLE, there is epidemiological evidence [74,98,153] that it may be cardioprotective, possibly by improving the lipoprotein profile [154] and improving vessel elasticity [155].…”
Section: Hydroxychloroquinementioning
confidence: 99%
“…HCQ is a weak base with the ability to increase intracellular pH; thus, HCQ may alter lysosome stability, suppress antigen presentation and cytokine synthesis, and inhibit TLR stimulation in vivo [15-17]. Theoretically, HCQ can suppress innate immune system activation by mucosal antigens via TLR inhibition, which results in reduced mucosal IgA-committed B cell proliferation [18].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that HCQ suppresses the production of numerous cytokines, including IL-6, IFN-α, TNF-α, by peripheral blood mononuclear cells and plasmacytoid dendritic cells [12, 15, 20-22]. Suzuki et al [23] found that treating cultured IgA1-secreting cells with IL-6 increased the production of Gd-IgA1 and the degree of the galactose deficiency by enhancing the already elevated activity of N-acetylgalactosamine (GalNAc)-specific sialyltransferase, which increased the sialylation of terminal GalNAc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been observed that the significant clinical improvement in SLE patients after hydroxychloroquine therapy correlated with reductions in IFNa levels [50]. Furthermore, treatment with hydroxychloroquine was associated with an impaired ability of pDCs from subjects with SLE to produce IFNa and TNFa upon stimulation with TLR7/9 agonists [51].…”
Section: Discussionmentioning
confidence: 99%